Reflecting on the Impacts of the 2013 coup in Central Africa Republic on Economic Security (International Journal of Scientific Research and Management (IJSRM), 2022)
This article aims to provide a concise overview of the impacts of the 2013 coup in Central Africa Republic (CAR) on human security with particular emphasis on economic security. CAR is a serial coup country and has been rocked by five successful military coups since its independence from France in 1960. The 2013 coup in CAR was the worst one as it ignited human catastrophe and a nosedive economy. The study is incentivised by the fact that although CAR has been a hippodrome of putsch there is scant in literature auditing how the coups affected human security. In order to have a better understanding of the phenomenon under investigation this study interrogates the concepts of coup and human security. The concept of human security has seven dimension and economic security is the major dimension of human security, hence this paper distinctly shows how the 2013 coup in CAR affected economic security and not the other six dimensions of human security which are food, political, personal, environmental, health and community security. The study observed that the 2013 coup resulted in the withdrawal of donors and investors and this resulted into low foreign direct investment. The coup also exposed the countries to external economic shocks which adversely affected the economy. The intrusion of rebel groups in the countries had negative economic ramification such as destruction of infrastructure and wanton looting and pillaging. The study used qualitative research instruments and documentary search was the primary method of collecting data.